(untitled) (Journal of Universal Science Research, 2025)
This article dwells on different kind of opinions which is given by scientists who worked with ornithonym in Uzbek languages. The study describes ornithonyms specific to Turkic languages ​​based on a study of bird names in the Uzbek language. In linguistics, mythological creatures in the form of birds are called "mythornithonyms", so they are analyzed as symbolic meaning in the article.